Extended and stable gene expression via nucleofection of MIDGE construct into adult human marrow mesenchymal stromal cells - Mok P.L.; Cheong S.K.; Leong C.F.; Chua K.H.; Ainoon O. (2024)
Indexed by WOS/ Scopus